OPTIMASI HYDROXYPROPYL METHYL CELLULOSE K15M DAN NATRIUM CARBOXYMETHYL CELLULOSE SEDIAAN BUCCAL FILM - Ardianes Firmansya; Lusi Nurdianti; Erin Yustira; Dwi Lista Ligarsari; Reiza Alvita Rafanida (Pharmacoscript, 2022)
ABSTRACT In 2020 the number of cases of Dengue Hemorrhagic Fever in Indonesia until the 49th week reached 95,893 cases and caused the death of around 661 people. This study aims to obtain the bestformula buccal film by optimizing the concentration of HPMC K15M and Na. CMC and evaluation of the characterization ofpreparations buccal film with 3 variations of concentration ratios against 3 formulas on HPMC K15M and Na polymer excipients. CMC include F1 0.67% : 0.33% ; F2 0.65% : 0.5% ; F3 0.33% : 0.67%. Research methods carried out bylaboratory experiments in vitro include optimization and manufacture ofpreparations buccal film and evaluation of the characterization ofpreparations buccal film. The results obtained by the three formulas met the standard with formula 3 being the best formula based on the results of viscosity 578.667±35.85, pH of wet mixture 6.24±0.08, folding resistance >300, surface pH 6.85±0.026, uniformityweight film 6 mg±0.22,thickness uniformity film 0.03±0.009 which resulted infilm a clear white, smooth and dry surface. Thus, it was concluded that from the 3 formulas with variations in the concentration of HPMC K15M and Na.CMC, the best formula was found in formula 3 and the results of the characterization evaluation met the requirements with the smallest standard deviation value. Keywords : Dengue Hemorrhagic Fever, HPMC K15M, Na.CMC, Buccal Film